The influence of physical fitness attributes on external demands during simulated basketball matches in youth players according to age category - Castillo, D.; Raya-González, J.; Scanlan, A. T.; Sánchez-Díaz, S.; Lozano, D.; Yanci, J. (Physiology & Behavior, 2021)
Highlights